2018
DOI: 10.1021/acsami.8b20158
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilding Postinfarcted Cardiac Functions by Injecting TIIA@PDA Nanoparticle-Cross-linked ROS-Sensitive Hydrogels

Abstract: Drug-loaded injectable hydrogels have been proven to possess huge potential for applications in tissue engineering. However, increasing the drug loading capacity and regulating the release system to adapt to the microenvironment after myocardial infarction face a huge challenge. In this research, an ROS-sensitive injectable hydrogel strengthened by self-nanodrugs was constructed. A hyperbranched ROS-sensitive macromer (HB-PBAE) with multiacrylate end groups was synthesized through dynamic controlled Michael ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 53 publications
(106 reference statements)
0
80
0
Order By: Relevance
“…The anti‐oxidation property of HBPAK was first assessed by DPPH assay. [ 6 ] The dark purple color of DPPH/HBPAK solution faded very apparently after 125 min compared to the DPPH ethanol solution (Figure 2C). Quantitative analysis by UV–Vis showed that along with time prolongation the absorbance of DPPH in the DPPH/HBPAK solution decreased monotonously (Figure S2A, Supporting Information), revealing the steady clearance of DPPH (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti‐oxidation property of HBPAK was first assessed by DPPH assay. [ 6 ] The dark purple color of DPPH/HBPAK solution faded very apparently after 125 min compared to the DPPH ethanol solution (Figure 2C). Quantitative analysis by UV–Vis showed that along with time prolongation the absorbance of DPPH in the DPPH/HBPAK solution decreased monotonously (Figure S2A, Supporting Information), revealing the steady clearance of DPPH (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…The use of stem cells faces several limitations such as low cell retention, time‐consuming of cell preparation, and potential allogeneic immune response, etc. [ 4 ] By contrast, the use of regenerative biomaterials can avoid these limitations, while the therapeutic performance can be well manipulated by using patches, [ 5 ] hydrogels, [ 6 ] scaffolds, [ 7 ] or particles. [ 8 ] In particular, the injectable hydrogels have the advantages of easy surgical operation and direct injection into the infarcted area, [ 9 ] leading to the most effective therapeutic effect on MI and restoration of the myocardial functions.…”
Section: Introductionmentioning
confidence: 99%
“…When injected into heart muscle, this hydrogel was found to improve cardiac functions by decreasing inflammation. [83] Click chemistry is another alternative to creating injectable hydrogels via chemical crosslinking. This approach provides short reaction times with high-yield chemoselectivity and can be performed under mild reaction conditions.…”
Section: Chemically Crosslinked Injectable Hydrogelsmentioning
confidence: 99%
“…In addition to ROS-triggered drug release, polymers with ROS-responsive bonds in their backbones or side chains are capable of consuming the excessive ROS produced by the MI. This reduces injury to the cardiac tissue, and has the potential for preventing and treating cardiovascular disease [133][134][135]. Yao et al reported a biodegradable elastomeric polyurethanes (PUTK) with ROS-responsive properties, which they made fibrous patches from.…”
Section: Inflammatory-responsive Drug Releasementioning
confidence: 99%